Assaying Homodimers of NF-κB in Live Single Cells - Martin, Erik W.; Chakraborty, Sayantan; Presman, Diego M.; Tomassoni Ardori, Francesco; Oh, Kyu-Seon; Kaileh, Mary; Tessarollo, Lino; Sung, Myong-Hee (Frontiers in Immunology, 2019)
NF-κB is a family of heterodimers and homodimers which are generated from subunits encoded by five genes. The predominant classical dimer RelA:p50 is presumed to operate as “NF-κB” in many contexts. However, there are several other dimer species which exist and may even be more functionally relevant forms in specific cell types. Accurate characterization of stimulus-specific and tissue-specific dimer repertoires is fundamentally important for understanding the downstream gene regulation by NF-κB proteins. In vitro assays such as immunoprecipitation have been widely used to analyze subunit composition, but these methods do not provide information about dimerization status within the natural intracellular environment of intact live cells. Here we apply a live microscopy technique termed Number and Brightness to examine dimers translocating to the nucleus in live fibroblasts after pro-inflammatory stimulation. This quantitative assay reveals that the RelA:RelA homodimers are more prevalent than previously thought. We found that the relative proportion of RelA:RelA homodimers versus other dimers can be perturbed by small molecule inhibitors known to disrupt the NF-κB pathway. Our findings show that Number and Brightness is a useful method for investigating NF-κB dimer species in live cells. This approach may help identify the relevant targets in pathophysiological contexts where the dimer specificity of NF-κB intervention is desired.